Factors Influencing Public Perception of Science - Taniya Jayani Koswatta; Gary Wingenbach; Holli R Leggette (Journal of Applied Communications, 2023)
Our literature review identified factors influencing public perception of science within the context of science communication. We analyzed 40 studies using an integrative literature review method and found that most research about public perception of science was conducted in developed countries’ contexts. We identified five categories of factors that influence public perception: Type of science, audience beliefs, socio-demographics, source of communication, and environment. We observed the type of science is the fundamental factor that determines the influence of other factors. Audience belief factors are the most influential factor theme. We also noticed that factors act as confounding and/or mediating variables that cannot separate them as a single factor to identify individual influence. To show the factors and their degree of influence on public perception of science, we developed a conceptual framework called the “ring of public perception of science.” The framework highlights the need for a holistic approach to examining the influence of factors affecting public perception of science. The proposed framework is based on a qualitative approach; further research is needed to validate relationships among these factors. Specifically, we recommend further research on context-specific factors because context is important to science communication, emerging environmental factors because of the changing landscape of science communication, and the use of social media to disseminate scientific information.
Keywords: Public perception; science communication; perception factors; science controversies